Interdisciplinary Studies: A Critical Review of the Concept, Paradigm, and Difficulties - Benlahcene, Badrane; Chatti, Chedli Baya; Hoque, Hossain Mohammed Naimul; El-Khal, Abdelaziz; Bakir, Ali (Journal of Islamic Thought and Civilization, 2024)
Interdisciplinarity constitutes one of the main drivers for the development of scientific knowledge as it contributes instimulating scientific research from different perspectives and methodologies and inreducing the isolation between disciplines. Although interdisciplinarity has become a common trend in scientific and academic circles of universities and research centers in recent years, the concept of interdisciplinarity remains largely controversial. The concept of interdisciplinarity is still fraught with confusion and ambiguity on many levels, including terminology, the model through which interdisciplinarity can be applied, and the methods or criteria through which interdisciplinarity can be detected. In this context, this research engages with the interdisciplinary studies through three main questions closely related to interdisciplinarity. The first question delves into the nature of interdisciplinarity research, scrutinizing prevalent ideas surrounding it. The second question explores proposed models for interdisciplinary research, their criteria, and examines whether a normative interdisciplinary model emerges from the literature. Whereas, the third question focuses on difficulties and opportunities facing interdisciplinary research in academic environments. In an attempt to answer these questions, several researchers from different disciplines participated in writing this research paper, where they engaged critically with the prevailing literature on interdisciplinarity, and presented a comprehensive theoretical review based on three levels of analysis.